Usefulness of Automated Latex Turbidimetric Rapid Plasma Reagin Test for Diagnosis and Evaluation of Treatment Response in Syphilis in Comparison with Manual Card Test: a Prospective Cohort Study - Tsuboi, Motoyuki (J Clin Microbiol, 2018)
The usefulness of an automated latex turbidimetric rapid plasma reagin (RPR) assay, compared to the conventional manual card test (serial 2-fold dilution method), for the diagnosis of syphilis and evaluation of treatment response remains unknown. We conducted (i) a cross-sectional study and (ii) a prospective cohort study to elucidate the correlation between automated and manual tests and whether a 4-fold decrement is a feasible criterion for successful treatment with the automated test, respectively, in HIV-infected patients, from October 2015 to November 2017. Study i included 518 patients. The results showed strong correlation between the two tests (r = 0.931; P < 0.001). With a manual test titer of ≥1:8 plus a positive Treponema pallidum particle agglutination (TPPA) test as the reference standard for diagnosis, the optimal cutoff value for the automated test was 6.0 RPR units (area under the curve [AUC], 0.998), with positive predictive value (PPV) of 92.5% and negative predictive value (NPV) of 99.4%. Study ii enrolled 66 men with syphilis. Their RPR values were followed up until after 12 months of treatment. At 12 months, 77.3% and 78.8% of the patients achieved a 4-fold decrement in RPR titer by the automated and manual test, respectively. The optimal decrement rate in RPR titer by the automated test for a 4-fold decrement by manual card test was 76.54% (AUC, 0.96) (PPV, 96.1%; NPV, 80.0%). The automated RPR test is a good alternative to the manual test for the diagnosis of syphilis and evaluation of treatment response and is more rapid and can handle more specimens than the manual test without interpersonal variation in interpretation.